Control rods' position history effect on the Indonesian multipurpose research reactor RSG-GAS operation and safety parameters. (February 2023) - Pinem, Surian; Luthfi, Wahid; Hartanto, Donny; Liem, Peng Hong
Abstract: The present work extends the analysis of the first working core of RSG-GAS to the burnup calculation. During the fuel management calculations of RSG-GAS, the control rods are usually assumed to be withdrawn from the core. Due to the exclusion of the control rod, it is hypothesized that the integral control rod worth shows significant differences compared to the experimental data. Therefore, a burnup calculation was performed in this study for the first core of RSG-GAS to evaluate the impact of operating control rods. The analyses were performed using continuous-energy Monte Carlo code, Serpent 2, and ENDF-B/VIII.0 nuclear data library for both cases with and without the inclusion of control rods. As a result, it is found that the calculated control rod worth, as well as the excess reactivity at the beginning of the cycle of the RSG-GAS second core from the burnup calculation considering the control rod position, agreed with the experimental data.